2021
DOI: 10.1016/j.maturitas.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis – An opportunistic infection in the aged immunocompromised individual: A reason for concern in COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…14 Other than environmental factors, uncontrolled diabetes mellitus, inappropriate steroid therapy, increased iron accumulation, and the damage caused by the COVID-19 virus may responsible for the MC. 4,11,15 In our study we reported MC in N=5 participants who were long stayed in hospital on oxygen support. All the MC positive participants belong to >60 years age and all had a weakened immune system.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…14 Other than environmental factors, uncontrolled diabetes mellitus, inappropriate steroid therapy, increased iron accumulation, and the damage caused by the COVID-19 virus may responsible for the MC. 4,11,15 In our study we reported MC in N=5 participants who were long stayed in hospital on oxygen support. All the MC positive participants belong to >60 years age and all had a weakened immune system.…”
Section: Discussionmentioning
confidence: 61%
“…Despite this, emerging complications associated with COVID-19 are being reported with the fungal infection mucormycosis becoming a serious issue in India due to its unprecedent surge and high morbidity. 4,10,11 The term MC collectively known "black mold" or "black fungus" in India is a fungal infection caused by the order of mucorales. Order: Mucorales is the group of the filamentous fungus, comprises about 20 pathogenic species which are further divided into 12 genera.…”
Section: Discussionmentioning
confidence: 99%
“…As the virus is foreign to the host, antigen presenting cells (dendritic cells, macrophages) present viral proteins to CD4 + T-helper (Th) cells via the major histocompatibility complex (MHC) class 1, resulting in the secretion of interleukin-(IL)-12 and interferon-γ to further trigger Th1 and natural killer cells [ 11 , 12 ]. In addition there is activation of the NF-kB signaling pathway resulting in pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, IL-17, IL-8) [ 13 , 14 ] which aid to attract neutrophils and monocytes which stimulate other pro-inflammatory cytokines and chemokines including monocyte chemoattractant protein-1 (MCP-1) [ 15 , 16 ]. Concurrently, IgM antibodies are generated lasting up to 12 weeks followed by IgG antibodies providing long lasting protection as a result of viral invasion [ 17 ].…”
Section: Introduction – Background Of Covid-19mentioning
confidence: 99%
“…The novel coronavirus strain, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged from Wuhan, China, in late December 2019 [7,8]. Rapidly, it spread around the globe and was declared a pandemic soon after [9].…”
Section: Introductionmentioning
confidence: 99%